Enhancing the Cost- and Time-Effectiveness of Field PV Module Inspection by UV-Fluorescence Imaging - Buerhop, Claudia; van Dyk, Eugene Ernest; Vorster, Frederik J.; Stroyuk, Oleksandr; Mashkov, Oleksandr; Mccleland, Jacqueline L.Crozier; Vumbugwa, Monphias; Hauch, Jens; Peters, Ian Marius (IEEE Journal of Photovoltaics, 2024)
This case study highlights the potential of UV fluorescence imaging as an emerging photovoltaic (PV) module inspection tool allowing the cost and time of the field inspection to be considerably reduced and opening a gateway to high-throughput operation. The application of UV fluorescence imaging is advanced beyond its reported capabilities by combining this technique with near-infrared absorption spectroscopy and electrical measurements. This combined approach allows for the identification and assessment of polymer backsheets and encapsulants, i.e., detection of polymer-related features (e.g., degradation, corrosion) as well as other anomalies (e.g., cell cracks and hot cells) with otherwise inaccessible cost- and time-effectiveness. In particular, 1890 PV modules in a 2 MWp PV power station show critical issues, including inner backsheet cracks and an insulation resistance below 1 MΩ identified for 40% of inspected strings and assigned to specific backsheet type populations. With an average throughput of 400-500 modules per hour, the present approach demonstrates a large potential for acceleration and cost-reduction of the PV plant inspection. It provides significant insights into system performance enabling proactive operation and maintenance of PV systems.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Backsheet; encapsulant; failures; high throughput; UV-excited fluorescence (UVF) imaging